A diffusion model decomposition of orientation discrimination in children with Autism Spectrum Disorder (ASD). Issue 2 (3rd March 2020) - Pirrone, Angelo; Johnson, Illin; Stafford, Tom; Milne, Elizabeth
ABSTRACT: Children with and without ASD performed an orientation discrimination task, in which the difficulty of the discrimination was equated across individuals. Behavioural results showed that subjects with ASD were slower in making a decision. A computational decomposition of data was performed and modelled parameters indicated that: (i) participants with ASD adopted a more conservative response criterion and (ii) motor response did not differ between groups. Our results confirm that differences in reaction times (RTs) and/or accuracy between participants with and without ASD in orientation discrimination may be related to differences in response conservativeness rather than in stimulus discriminability, in line with data previously reported from adults. This result has important implications for studies that have claimed impairments/enhancements in ASD on the basis of differences in RTs and/or accuracy alone.